Pengaruh Struktur Organisasi, Rentang Kendali dan Budaya Organisasi Terhadap Kinerja Pegawai Badan Penyelenggaraan Pelayanan Perizinan Terpadu Kota Kendari - Rola Yona Anto (e-JKPP, 2015)
This study aims to examine and analyze the effect of organizational structure, span of control and organizational culture on employee performance Administering Agency Licensing Service Kendari. This study used a quantitative approach, the technique used in collecting the data is to use a questionnaire addressed to the respondent and informant interviews, as well as literature. The results of this study indicate that: (1) organizational structure give the effect of 39.2% on employee performance on Administering Agency Licensing Service Kendari; (2) Full Range of 38.0% impact on employee performance on Administering Agency Licensing Service Kendari; (3) organizational culture did not impact significantly by 03.7% on employee performance on Administering Agency Licensing Service Kendari; (4) Organizational Structure, Organizational Culture Full Range and simultaneously give the effect of 67.2% on employee performance Administering Agency Licensing Service Kendari. This means that in addition to these three variables there are other variables that can affect employee performance Administering Agency Licensing Service Kendari which amounted to 33.8%, which was not examined in this research.